CORRELATION BETWEEN TRANSEPIDERMAL WATER LOSS (TEWL) ON NON-LESIONAL SKIN AREA AND CLINICAL SEVERITY OF ATOPIC DERMATITIS - , ADELLIA DIAN PERMATASARI, dr. Niken Trisnowati, M.Sc., Sp.KK. ([Yogyakarta] : Universitas Gadjah Mada, 2014)
-